2001
DOI: 10.1093/ajcn/73.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of anorexia nervosa patients assessed by underwater weighing and skinfold-thickness measurements before and after weight gain

Abstract: Body fat estimation by skinfold-thickness equation appeared to be as accurate as underwater weighing. The refeeding program led to a significant increase in body weight, of which 55.5% was body fat. The mean ratio of fat-free mass to fat mass at the end of the treatment was 3.4:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
4
30
0
4
Order By: Relevance
“…With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery. The studies available in the literature also indicate that FM represents 21 -77% of the weight gained (Russell & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001;Grinspoon et al, 2001), while the number of calories needed to put down body mass seems to increase during refeeding (Salisbury et al, 1995). Nevertheless, despite the widespread use of anthropometric techniques for the assessment of nutritional status, only a few studies have so far examined the changes in skinfolds and circumferences which occur during weight recovery (Forbes et al, 1984;Nuñez et al, 1994;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery. The studies available in the literature also indicate that FM represents 21 -77% of the weight gained (Russell & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001;Grinspoon et al, 2001), while the number of calories needed to put down body mass seems to increase during refeeding (Salisbury et al, 1995). Nevertheless, despite the widespread use of anthropometric techniques for the assessment of nutritional status, only a few studies have so far examined the changes in skinfolds and circumferences which occur during weight recovery (Forbes et al, 1984;Nuñez et al, 1994;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The studies available in the literature also indicate that FM represents 21 -77% of the weight gained (Russell & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001;Grinspoon et al, 2001), while the number of calories needed to put down body mass seems to increase during refeeding (Salisbury et al, 1995). Nevertheless, despite the widespread use of anthropometric techniques for the assessment of nutritional status, only a few studies have so far examined the changes in skinfolds and circumferences which occur during weight recovery (Forbes et al, 1984;Nuñez et al, 1994;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001). In particular, the issue has recently been evaluated by Orphanidou et al, (1997) and Probst et al, (2001) in a more systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…Este fato chama a atenção, uma vez que quantidade extremamente baixa de gordura corporal pode estar associada a algumas desordens nutricionais como a aneroxia nervosa, principalmente entre adolescentes do sexo feminino e a desnutrição protéico-energética afetando o processo de crescimento físico (32)(33) . Outro aspecto importante desse estudo foi à quantidade elevada de crianças que apresentaram excesso de gordura corporal (~28% para os meninos e ~14% para as meninas).…”
Section: Discussionunclassified
“…Esses resultados são bastante preocupantes, uma vez que valores de gordura corporal relativa superiores a 25% e 30%, em meninos e meninas, respectivamente, estão associados a um alto risco de desenvolvimento de doenças cardiovasculares, hipertensão, hipercolesterolemia e hiperlipidemia (2)(3) . Além disso, os resultados encontrados foram bastante superiores ao relatados por outros estudos no Brasil (33)(34) , sugerindo uma forte associação desses resultados com as características econômicas e culturais da amostra (36) .…”
Section: Discussionunclassified
“…Podvodna metoda određivanja procenta telesnih masti se smatra referentnom metodom za procenu telesnog sastava jer ima veliku pouzdanost i validnost [28]. Godinama je smatrana zlatnom metodom zbog moguće male greške u proceni Db (0,0015 g/ml ili oko 0,7 %BF).…”
Section: Metoda Podvodnog Merenja (Hidrodenzitometrija)unclassified